Preparación del ácido-3,5 dipropionilamino-2, 4, 6-triyodobenzoico I131 - Mitta, A.E.A.; Huala, H.E.; Camín, L.L. (Comisión Nacional de Energía Atómica (CNEA), 1968)
Fil:Mitta, A.E.A. Comisión Nacional de Energía Atómica (CNEA). República Argentina